Analisis Ketergantungan China-Sri Lanka dalam Proyek Pembangunan Pelabuhan Hambantota Tahun 2007-2017 - Nurjayanti, Vivi Ariesta (Nation State: Journal of International Studies, 2020)
The purpose of this research is that the reader can find out the problem of Sri Lanka's dependence on China in the Hambantota Port development project which ultimately ended up as a debt trap. In this research authors used qualitative research methods. And from the results of research that has been done, it is found that basically the cooperation carried out by China and Sri Lanka is a collaboration between hegemon countries and third world countries. Debt trap diplomacy itself has close links with other Chinese policies, namely the Belt and Road Initiative, this policy focuses on infrastructure development which includes the construction of railroad networks, the construction of roads to ports located in the territories of other countries and has a strategic position and will good impact for the achievement of Chinese interests in realizing the "new Silk Road". Sri Lanka proposed cooperation to build the port of Hambantota with the aim of helping to improve Sri Lanka's economy. Cooperation that is expected to have a positive impact on Sri Lanka actually brings disaster, because it leads to a debt trap that makes Sri Lanka must hand over the port of Hambantota to the China’s government.